Citizenship and freedom - Tonet, Ivo (Universidade Estadual Paulista / UNESP, 2009)
This paper intends to show that the same act that is in the origin of the social relations in the capitalist system is in the foundation of citizenship. And that, by having its source in the social inequality, the citizenship in consequently a partial, limited and formal way of freedom. Men effectively free could only exist if and when the present social order be surpassed by another one whose foundations are the collective work. Although it is very hard to find the necessary means, the horizon of a true left must be the emancipation and not the citizenship.